West Nile and Usutu viruses: current spreading and future threats in a warming northern Europe - Laverdeur, Justine; Amory, Hélène; Beckers, Pablo; Desmecht, Daniel; Francis, Frédéric; Garigliany, Mutien-Marie; Hayette, Marie-Pierre; Linden, Annick; Darcis, Gilles (Frontiers in Virology, 2025)
Climate change heavily threatens planetary and human health. Arboviral infections are best studied using the One Health concept, due to their reliance on complex interactions between environmental factors, arthropod vectors and vertebrate hosts. This review focuses on two arboviruses, namely West Nile Virus (WNV) and Usutu Virus (USUV), both causing emerging public health issues in northern Europe. They are both maintained in an enzootic cycle involving birds and Culex spp mosquitoes. WNV has demonstrated its sensitivity to the consequences of climate change and there is already evidence that global warming contributes to its expansion in Europe. Future WNV indigenous transmission in northern Europe is therefore plausible. Usutu is a lesser known arbovirosis, sharing similar vectors and hosts as WNV. USUV has a similar geographic expansion to WNV, exhibiting some level of co-circulation. It is therefore crucial to monitor these viruses in the hitherto relatively spared regions of northern Europe.